The Effect of Oral Health Educational Intervention Program among Mothers of Children aged 1-6, Based on the Theory of Planned Behavior - Raheleh Soltani; Gholamreza Sharifirad; Behzad Mahaki; Ahmad Ali Eslami (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Oral self- care is an important aspect of lifestyle and a serious public health issue. Purpose: This study aimed to evaluate the effect of an educational program based on the theory of planned behavior (TPB) on the mothers and children's oral self-care behaviors. Materials and Method: This quasi-experimental study was conducted on 148 mothers and their children (1-6 years) who referred to the health centers of Tabriz, Iran ; divided into two groups of intervention (n=74) and control (n=74). Data were collected through a questionnaire that included demographic characteristics, oral self-care behaviors, and structures of TPB. Both groups completed questionnaires before, immediately, 3 and 6 months after the intervention. The experimental group received three educational sessions, each session held for 120 minutes. The educational methods such as lectures, group discussion, and demonstrations were used. Data were analyzed using SPSS (ver18) software and Chi-square, Independent samples t-test and repeated measure ANOVA at the significant level of < 0.05. Results: Before the intervention, there were no statistically significant differences between both groups in oral self -care behaviors and structures of TPB (p> 0.05). Immediately, 3 and 6 months after the intervention the mean scores of oral self-care behavior presented a significant increase in both mothers and their children in the intervention group (p< 0.001). Six months after the intervention, brushing children's teeth twice a day increased significantly from 8.1% (6/74) to 55.4% (41/74) in the experimental group (p< 0.001). At immediately, 3, and 6 months after the intervention, the mean scores of mothers' attitude, subjective norm, perceived behavioral control and intention towards the children's oral health were significantly increased in the experimental group compared to the control group (p< 0.001). Conclusion: According to the results of this study, intervention based on the theory of planned behavior promotes the oral self-care behavior both in mothers and in their children.